Penguatan Pendidikan Karakter Di SMA Negeri 9 Kota Ternate - Yusri A. Boko; Hi. Talib Abas (Peneliti.net, 2022)
The aims of this study are 1) to describe the strengthening of Character Education in State Senior High School 9 Ternate City, 2) describe the inhibiting factors of Character Education in State Senior High School 9 Ternate City. This research is a qualitative research. The research location is at State Senior High School 9 Ternate City. The results of this study indicate that strengthening character education in State Senior High School 9 Ternate City is developed through two activities, namely intracurricular and extracurricular activities. Intracurricular includes planning, implementation, and evaluation in a structured manner. Meanwhile, extracurricular strengthening is carried out through; a) Basic Leadership Training, b) Scouting, with scouting students are taught to have high discipline, the spirit of defending the country, mutual cooperation, and love for the homeland, c) interpreneurship, the attitude of students working together, working hand in hand to seek funds Intra-School Student Organization (OSIS). The positive impact of strengthening character education at State Senior High School 9 Ternate City can be explained through: a) there is motivation for students to do good or be honest at all times, b) not break promises or lie between others, c) respect and respect those who are more parents, especially teachers, d) always grateful for every blessing given by God, e) praying in congregation even though there are still many left behind, f) caring for a clean learning environment, g) accustomed to living together in groups, both at school and in their environment. stay, h) have an independent attitude, i) trained to be a leader in the future, j) likes to help friends in difficult circumstances. The inhibiting factors for character education at State Senior High School 9 Ternate include; 1) school environment; Schools as formal spaces are still lacking, for example, there is no theater stage in the school yard. Whereas stage theater can improve students' expression (character); 2) family environment; Most of the parents of State Senior High School 9 Ternate are farmers.